Removal of fluoride from water using thermally treated dolomite and optimization of experimental conditions using response surface methodology - Kim, Mun Ju; Hong, Seung Hee; Lee, Jae In; Lee, Chang Gu; Park, Seong Jik (Desalination and Water Treatment, 2019)
This study was performed to identify an economical but highly effective adsorbent for the removal of fluoride. Dolomite was thermally treated to improve its adsorption capacity for fluoride; dolomite thermally treated at 800°C (DTT-800) was superior to that treated at other temperatures. The maximum fluoride adsorption capacity of DTT-800 was 163.7 mg g–1, which was superior to that of other adsorbents reported in the literature. Fluoride adsorption onto DTT-800 was characterized by chemisorption, multi-layer adsorption, and an endothermic reaction. Response surface methodology was employed to investigate the influence pH, ionic strength, reaction temperature, and time on fluoride adsorption; these parameters were optimized to maximize the adsorption process. pH and ionic strength had a negative effect, while reaction temperature and time had a positive effect on fluoride adsorption. The influence of all four parameters was significant (p <0.001). Highest fluoride adsorption (165.91 mg g–1), was obtained under the following conditions: PH 4.57, ionic strength 7.45 mM, temperature 28.30°C, and contact time 58.33 h. This study demonstrated that DTT-800 is a low-cost, natural, and abundant material for the removal of fluoride from aqueous solutions
Keywords: Adsorption; Dolomite; Fluoride; Optimization; Response surface methodology; Thermal treatment